Evaluation of Maxillary and Sphenoidal Sinuses' Volume and Bizygomatic Width Using Cone Beam Computed Tomography - A Promising Tool for Sex Determination - Indhumathi Sivasamy; Pinakapani Ramakarishna; Satyapal Johaley; Sarbani Deb Sikdar; Shilpa K. Jain; Raj Kumar Diwan (Wolters Kluwer Medknow Publications, 2024)
Introduction: Sex determination is a critical step in the identification of individuals in forensic medicine. Cone beam computed tomography (CBCT) is an excellent tool for analyzing the volume of paranasal sinuses that can be used for sex determination. Aim: To measure and compare sexual dimorphism in the bizygomatic distance and the volumes of the maxillary and sphenoidal sinuses on CBCT images and evaluate their significance in sex determination. Materials and Methods: A retrospective study was conducted using 102 CBCT scans, which were analyzed using ITK-SNAP software to determine the volumes of the maxillary sinus and sphenoidal sinuses. The bizygomatic width was measured in the axial section. The differences in the volumes of the maxillary and sphenoidal sinuses and bizygomatic width were assessed for their significance in sex determination. The study population was divided into male and female groups (51 males and 51 females). The age range was 20-75 years. Statistical analysis was conducted using independent t-tests and discriminant functional analysis. Results: Statistically significant differences were observed in bizygomatic width, right maxillary sinus volume, left sphenoidal sinus volume, total maxillary sinus volume, and total sphenoidal sinus volume (P < 0.05). Conclusion: Adult paranasal sinus volumes and bizygomatic width analyzed using CBCT may be useful for sex determination in forensic investigations.